STRATEGI SILVIKULTUR UNTUK MENINGKATKAN KELESTARIAN PRODUKTIVITAS HUTAN ALAM DI INDONESIA (Silvicultural Strategy to Improve Productivity of the Natural Forest in Indonesia) - , Maman Sutisna ([Yogyakarta] : Fak. Kehutanan UGM, 2000)
Natural foret management in Indonesia is not yet fully implemented, indicated by the followng facts: the continous decline of forest area due to forest fire, lack of implementation in timber stand improvement in the production area, nonexistence of multipurpose management in protection and recreation forests, and insufficient protection in conservation forest from destructive activities. Neglecting the integrated forest management and appropriate silvicultural techniques results in failures in managing forest in the field. The sequence of the integrated forest management is: (I) forest inventory to define appropriate silvicultural technique, (2) territory organisation to achieve efficiency of appropriate silvicultural implementation, (3) area and stand security through physical and social measures, (4) appropriate silvicultural techniques. Apropriate silvicultural techniques are based on: (I) forest function, (2) the condition offorest vegetation, (3) site condition (soil type. slope), (4) accessibility for management and disturbance, (5) management objective, (6) management ability, (7) social pressure. The indicator of the natural forest management is sustainability of maximum benefit both in the production, protection, and conservation forests. Regarding wood production, productivity of the production area in the natural forests, can be improved by simple ways, e.g. one application of refinement followed by 4 to 5 times selective crown liberation/thinning known as Binapilih techniques. In Binapilih I, diameter increment ofmeranti crop trees can be improved from 0.5 to 1,5cm/yr which corresponds to an improvement from 1.5 mJ/halyrto 10mJ/halyr. In Binapilih2, diameter increment of meranti crop trees can be increased from 0.5 cm/yr to 2 cm/yr which eqivalent to an improvement from 1.5m3/halyrto 15m3/halyr.These Binapilih techniques can increase financial profit of timber company up to 10 to 15 times higher compared with that of untended stand. There are still a number of forest political challenges to increase motivation of forest managers to maintain their natural forest properly, i.e. increasing time length of concession contract at least twice the felling cycle (70 years), desentralization of aministering the production forest to the otonomous local government, and the need of cooperation in forest management between concession holders and local communities.